2010
DOI: 10.1007/s10911-010-9177-x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-Induced Epithelial-Mesenchymal Transition in Breast Cancer

Abstract: Matrix metalloproteinases (MMPs) degrade and modify the extracellular matrix (ECM) as well as cell-ECM and cell-cell contacts, facilitating detachment of epithelial cells from the surrounding tissue. MMPs play key functions in embryonic development and mammary gland branching morphogenesis, but they are also upregulated in breast cancer, where they stimulate tumorigenesis, cancer cell invasion and metastasis. MMPs have been investigated as potential targets for cancer therapy, but clinical trials using broad-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
347
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(370 citation statements)
references
References 144 publications
13
347
0
10
Order By: Relevance
“…Consistent with this idea, gain in hSETD1A gene copy number is detected in approximately 45% of breast tumors (39). Finally, increased MMP activity is commonly observed in breast cancer cells and promotes a variety of cellular activities including proliferation, migration, and invasion (33,(40)(41)(42)(43). Taken together, these facts prompted us to investigate a possible link between hSETD1A, H3K4me3, MMP expression, and metastatic breast cancer phenotype.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Consistent with this idea, gain in hSETD1A gene copy number is detected in approximately 45% of breast tumors (39). Finally, increased MMP activity is commonly observed in breast cancer cells and promotes a variety of cellular activities including proliferation, migration, and invasion (33,(40)(41)(42)(43). Taken together, these facts prompted us to investigate a possible link between hSETD1A, H3K4me3, MMP expression, and metastatic breast cancer phenotype.…”
Section: Introductionmentioning
confidence: 69%
“…MMPs are widely known as critically important in promoting cancer cell migration and invasion by degrading extracellular matrix proteins (33,(40)(41)(42)(43). As previous work from our group indicated that hSETD1A was required for MMP7 expression in colorectal tumor lines (26), we examined a number of MMP genes that could be potentially affected by hSETD1A knockdown in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of molecules with the ability to induce EMT in physiological and pathological conditions are the metalloproteinases (MMP) (reviewed in [51]). The role of MMPs as EMT inducers has been described in kidney, lung, ovary, oral, and mammary epithelium [52][53][54][55][56][57].…”
Section: The Epithelium To Mesenchymal Transitionmentioning
confidence: 99%
“…8,9 Identifying proteases that drive tumor progression and metastasis, and defining their specific mechanisms of action, can potentially reveal novel druggable targets and underexplored avenues for slowing or halting the spread of metastatic disease. 10 Moreover, as extracellular molecules with binding sites for highly specific substrate ligands, secreted proteases are more amenable to pharmacological inhibition that are many oncogenic signaling pathways within the cell.…”
mentioning
confidence: 99%